PENYULUHAN KELUARGA SAKINAH, MAWADDAH,WARAHMAH - Unggul Priyadi (Asian Journal of Innovation and Entrepreneurship, 2013)
Having a harmonious family is harmonious is the desire of every couple who hasbeen married. But to realize it is not an easy task. Especially in the midst of the timesnow, run to build a harmonious family, can maintain the integrity of the household isalready a remarkable achievement. Marriage is a series of worship to Allah wa Ta'alaSubhaanahu in which there are many virtues and great rewards reaped by the couple.However, we have encountered on our brothers had misjudged a marriage, even amongthose not understand the science though. We chose this program because at thenumber of early marriages that occurred in Hamlet Ngaglik RT / RW 02/04, where it isstill need knowledge to raise a family sakinah, mawaddah, warahmah. The program isselected to provide knowledge to the Hamlet Ngaglik RT / RW 02/04 how to raise afamily sakinah, mawaddah, warahmah. The event begins with a number of people who dothe data collection of early marriage. This was followed by the provision of material firstcounseling given by religious leaders Hamlet Ngaglik RT / RW 02/04, Mr Abdusyakur.The next stage is done by giving the material a second extension to the award of thesecond material which is filled by the head of KUA Mr Siswanto. After giving the laststage of extension materials are questionnaires, in order to assess how the familysituation of Dukuh Ngaglik RT / RW 02/04, where the family will meet the criteriasakinah, mawaddah, warahmah awards. While the result is the public able to understandhow to foster family became a family sakinah, mawaddah, warahmah.